EFEKTIVITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI DESA BATANG KULIM KABUPATEN PELALAWAN - Andry, Hendry (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2021)
This descriptive survey research aimed to analyze the effectiveness of collection of Earth and Building tax done by The Financial Management Agency and Regional Assets (BPKAD) in Batang Kulim, Pelalawan. The data were collected through questionnaires, observation and interview. They were analyzed by using the indicators of effectiveness theory. It was found that there were discrepancy among the data. Finally, although the result of questionnaire showed quite effective, but the overall effectiveness of land and building tax collection in Batang Kulim, Pelalawan indicated ineffective.